Effect of Market and User Characteristics on the Expected Quality of Taxi Service - Nađ, Andrea; Tica, Slaven; Milovanović, Branko; Živanović, Predrag; Bajčetić, Stanko (Promet - Traffic&Transportation, 2022)
The taxi system is one of the most famous and de-veloped subsystems of flexible passenger transport. To reach the goal of the system achieving maximum produc-tion efficiency, the management focus is directed at users and service quality (SQ). The SQ can have several forms: expected, targeted, delivered, and perceived SQ. We ex-amine the expected SQ, expressed through the users’ at-titudes about the importance of the defined parameters of the SQ, which represent the users’ expectations from the taxi system. The analysis included the data from the conducted studies in three selected taxi systems. The aim of this paper was to determine the effect of market and selected user characteristics on the user expectations, applying the Chi-Square Test. We conclude that the spe-cific market and certain user characteristics affect the user expectations of the taxi system. There is a moderate effect on the employed users, pensioners, and daily users of the taxi system. When it comes to the users who use the taxi system several times a month and week, there is a less significant effect. Other user categories have no sig-nificant correlation with the selection of the parameters of the SQ in the taxi system.